Analisis Kebijakan dan Implementation Gap dalam Merespon Masalah Illegal logging di Kecamatan Atu Lintang, Aceh Tengah - Cut Maya Aprita Sari; Ayu Mahara (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2019)
Atu Lintang forest was known as a critical area in Central Aceh which was experience a great damaged due to continuous illegal logging activities. This activities impacted on societal lives, such as floods, landslides, and the decline of wild animal in residential areas. So far, the Central Aceh regional government has implemented a legal and reforestation policy to deal with the problem of illegal logging. However, this policy has not succeeded in suppressing the number of illegal logging cases that have occurred. Therefore, this study aims to find out the implementation gap and barriers of the Central Aceh Regency government in dealing with the problem of illegal logging in Atu Lintang District. This study uses a descriptive qualitative approach. The data were obtained through field research by interviewing relevant informants and library studies by examining various relevant text sources. Through theoretical analysis using David Easton's political system theory (1953) and implementation gap theory (Andrew Dunsire, 1978). The results of this study indicate that the government is not capable in dealing with the problem of illegal logging. From the government side, implementation gap was occurred which caused by bad policy, namely the inability of the government to form appropriate policies: bad execution and bad luck in implementing policies. From the community side, the obstacle that arises is the low level of public understanding about the importance of protecting forests.